Sustainable development of climate-resilient aquaculture and culture-based fisheries through adaptation of abiotic stresses: a review - R. Abisha; Kishore Kumar Krishnani; Kapil Sukhdhane; A. K. Verma; Manoj Brahmane; N. K. Chadha (Journal of Water and Climate Change, 2022)
Climate change is an inevitable event that obstructs the output of aquaculture farms and culture-based fisheries in open waters. It poses a serious threat to global food security, altering biodiversity, ecosystems, and global fish output by displacing fish stocks from their natural habitats. When compared to freshwater aquaculture, marine/coastal aquaculture is more affected. To combat the effects of climate change, several mitigation methods and adaptations are being implemented, emphasizing future demands of affordable protein. Selective breeding, species diversification, and aquaculture systems like integrated multi-trophic aquaculture, aquaponics, and recirculating aquaculture system are some of the most widely accepted and adapted solutions. Further research on intervention in seed and feed in terms of quality improvement, bioresource utilization, and technological and genetic improvement is required. Climate change policies from the government are also essential. The present study differs from previous reviews by portraying the various abiotic stress factors contributing to the drastic climate change, encompassing adaptation strategies followed in distinct aquaculture sources such as freshwater, inland saline water, brackish water, coastal waters, and culture-based capture fisheries with its future implications. HIGHLIGHTS Climate-resilient aquaculture adaptations are necessitated to sustain production and to uphold socio-economic conditions.; This review provides insights into climate-resilient aquaculture and culture-based fisheries.; This review provides linkage between abiotic stressors causing climate change and building resilience for adaptation to climate change.;